Pengaruh struktur modal, ukuran perusahaan, pertumbuhan perusahaan, dan profitabilitas terhadap harga saham pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia - Evania, Linda; Kentris Indarti, Maria Goreti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of capital structure, firm size, firm growth, and profitability on stock prices. The financial ratios studied are Debt to Equity Ratio, Size, Sales Growth, and Return on Equity as independent variables and stock prices as variables. dependent. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 using a purposive sampling technique with certain criteria and systematics aimed at obtaining a representative sample. The data used is secondary data. The number of samples used in this study is 60 companies with a period of 3 years. The statistical method used in this research is multiple linear regression method. The result showed that capital structure had a negative effect on stock prices, but firm size had no effect. as hypothesized, firm growth and profitability had a positive effect on stock prices.